Risk Factors and Etiology of Neonatal Sepsis at Baghdad Hospitals, Iraq: عوامل الخطر المرتبطة بتطور تعفن الدم عند حديثي الوالدة في مستشفيات بغداد، العراق - Turki, Salwa Ghazi; Abed Alkendi , Marwa Najy (Iraqi National Journal of Nursing Specialties, 2026)
Objective(s(: To determine risk factors and etiology associated with development of neonatal sepsis at Baghdad hospitals, Iraq.Methods: The descriptive analytical case control study design technique entails was used for conducting research on neonatal care units in Baghdad Governorate in order to identify the causes and risk factors leading to neonatal sepsis. Where it was implemented during the period from November 20th, 2022, to 1st June 2023. The data analyzed by using package SPSS. version 22.Results: Newborns who developed sepsis with their mother's data and control group were 94 neonates per group. Evaluation of risk factors showed that mothers with a first or second child (parity 1-2) were significantly associated with neonatal sepsis (P = 0.016) and mothers were more likely to have neonatal sepsis on their children (2.092) fold high risk than mothers with multiple births (multiparity). On the other hand, women who undergoing caesarean section, high blood pressure, bleeding disorder, urinary tract, premature rupture of membranes, and perinatal fever were (6.4, 2.279, 2.303, 4.119, 3.476, 2.943 times respectively) more likely to have sepsis. In terms of neonatal risk factors, infants born preterm, before 37 weeks gestation, birth weight less than 2500 grams (18.0), neonatal age (7-28 days), preterm score